UTILIZATION OF CORN COB WASTE AS COMPOSITE BOARD (FIBERBOARD) WHICH WILL BE USED AS SOUNDPROOF WALLS - Irwan, Yusril; Hurahman, Agus Patih; Amanullah, Muhammad Naufal (Universitas Mercu Buana, 2025)
Currently, Ciherang Village in Nagreg Regency has abundant corn plantations that serve as the primary livelihood for its residents. The villagers mainly utilize corn kernels for food processing or resale, while the corn cobs are partially used to produce briquettes. However, a large amount of corn cob waste remains unutilized, often discarded into rivers or left in front of houses, creating an unpleasant sight and odor.One potential solution is to process the corn cob waste into composite boards (fiberboard), which are planned to be used as soundproofing materials for rooms or motor vehicles. This initiative aims to promote waste utilization, recycling, and contribute to the green economy. To assess the soundproofing characteristics of the fiberboard, several tests will be conducted, including acoustic testing, Scanning Electron Microscopy (SEM) analysis, vibration, density, recovery, and water absorption testing.